Contextualising Queer Theory: Sex and Gender in the American Philosophy of Judith Butler v. Native American Theory and Cultures - Holly May Treadwell (Janeway JS, 2020)
As the scholarship and conversation regarding LGBTQ+ issues expand and gain more visibility, there is still one group and one history especially that is left out of this discussion: indigenous cultures. Indeed it is primarily white writers who are credited for opening up the definition of concepts such as gender, and although such writers have without a doubt helped bring the issue into the focus of contemporary society, the views they are representing are not new and certainly do not originate in any white, Western theory. This paper explores Judith Butler’s theorisations surrounding gender and sex from her book, Gender Trouble, in comparison to Native American scholarship and culture. Butler’s writing has transformed the way in which contemporary society views gender and sex by bringing the idea of performativity into mainstream media, but this article aims to show that the ideas and concepts she discusses in her work are not new; many Native American societies have held such views for centuries. Views and concepts discussed in this article include the multifariousness of sex (that is, sex as a spectrum rather than a binary, and sex as being non-definitive of person), and the diversity of gender (specifically gender as a social construct, as independent from sex, derived from character rather than biology, and as variable and fluid). By examining quotes from Butler alongside examples of the existence and indeed prominence of these views in Native American cultures, this article demonstrates that the concepts outlined by Butler can be seen to pre-exist her theorisations by centuries in both Native American culture and Indigenous scholarship.